Surgical management of glaucoma secondary to idiopathic elevated episcleral venous pressure - Zia Sultan Pradhan; Ashish Kuruvilla; Pushpa Jacob (Oman Journal of Ophthalmology, 2015)
Idiopathic elevated episcleral venous pressure is characterized by dilated episcleral veins and open angle glaucoma. Trabeculectomies in these eyes are often complicated by uveal effusions (intraoperative or postoperative) at nonhypotonous pressures. We highlight the ability to avoid the need for sclerostomies by preventing intraoperative shallowing of the anterior chamber and the use of tight scleral sutures which should be adjusted postsurgery to gradually reach the target intraocular pressure in a step-wise manner.